2018
DOI: 10.1017/s0007123417000655
|View full text |Cite
|
Sign up to set email alerts
|

Violence, Empathy and Altruism: Evidence from the Ivorian Refugee Crisis in Liberia

Abstract: In regions plagued by reoccurring periods of war, violence and displacement, how does past exposure to violence affect altruism toward members of different ethnic or religious groups? Drawing on theories of empathy-driven altruism in psychology, this article proposes that violence can increase individuals’ capacity to empathize with others, and that empathy born of violence can in turn motivate helping behavior across group boundaries. This hypothesis is tested using data on the hosting behavior of roughly 1,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 53 publications
3
61
1
Order By: Relevance
“…That is, individuals may be more likely to engage in altruistic behaviours when they have experienced adverse life events compared to those who have not experienced negative life events. Such findings have been reported among HIV-positive individuals (Reeves et al, 1999), as well as cancer (Ferrell et al, 1995), sexual assault (Stidham et al, 2012) and war survivors (Hartman and Morse, 2015). For example, in qualitative research HIV-positive individuals, they "repeatedly voiced their desire to help others" (Reeves et al, 1999, p. 353).…”
Section: The Role Of Empathymentioning
confidence: 88%
See 1 more Smart Citation
“…That is, individuals may be more likely to engage in altruistic behaviours when they have experienced adverse life events compared to those who have not experienced negative life events. Such findings have been reported among HIV-positive individuals (Reeves et al, 1999), as well as cancer (Ferrell et al, 1995), sexual assault (Stidham et al, 2012) and war survivors (Hartman and Morse, 2015). For example, in qualitative research HIV-positive individuals, they "repeatedly voiced their desire to help others" (Reeves et al, 1999, p. 353).…”
Section: The Role Of Empathymentioning
confidence: 88%
“…Extending these findings to settings of protracted intergroup conflict, Hartman and Morse (2015) studied altruistic motivations in a diverse post-conflict society. Similar to ABS, they proposed that 'empathy born from violence' can result in increased altruism toward both ingroup and outgroup members.…”
Section: Helping In An Intergroup Contextmentioning
confidence: 95%
“…It is therefore difficult to know whether the higher overall level of altruism in the population is due to effects of war experiences on altruism, or higher levels of altruism showed towards refugees at the hands of fellow refugees. Indeed, previous research has shown that exposure to war-related violence under some circumstances can increase positive attitudes towards refugees (Hartman & Morse, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One of the prime motivations for the present study is to determine whether there is meaningful variation in attitudes within host countries. In deriving expectations regarding the roots of variation in support for hosting refugees, we begin with the observation that the vast majority of refugees fleeing conflict zones, including those exiting Syria, settle in countries that have themselves a meaningful history of violence (Hartman & Morse, 2018). It stands to reason, therefore, that host population's attitudes towards hosted populations reflect their own personal experiences with conflict.…”
Section: Experience With Violence and Displacementmentioning
confidence: 99%
“…At their core, these studies reflect a diffuse set of logics which center upon the potential for growth in prosocial behaviors in the aftermath of trauma. In the context of refugee crises, these prosocial behaviors and attitudes reflect a mechanism of empathy-driven altruism, which transcend identity boundaries (Hartman & Morse, 2018).…”
Section: Experience With Violence and Displacementmentioning
confidence: 99%